2005
DOI: 10.1108/00483480510591462
|View full text |Cite
|
Sign up to set email alerts
|

Goal orientation and organizational commitment as explanatory factors of employees' mobility

Abstract: Purpose -To provide a further examination into the explanatory factors of employees' mobility for organizations wishing to improve performance by keeping right employees judging from their goal orientation and organizational commitment. Design/methodology/approach -The multivariate statistical methods (MANOVA) together with a longitudinal design are used to test the hypotheses generated from the theory with data gathered from two Taiwan-based financial institutions. Findings -Suggests that those who quit for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 41 publications
3
52
1
1
Order By: Relevance
“…Therefore, future research should focus on the relationship between the motivational climate, goal orientation, and employee turnover intention (Hom, Caranikas-Walker, Prussia, & Griffith, 1992). Instead of quitting a job to seek out greater challenges (Lin & Chang, 2005), mastery-oriented individuals might consider staying because of the employee benefits of a mastery climate for improving their work life quality.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, future research should focus on the relationship between the motivational climate, goal orientation, and employee turnover intention (Hom, Caranikas-Walker, Prussia, & Griffith, 1992). Instead of quitting a job to seek out greater challenges (Lin & Chang, 2005), mastery-oriented individuals might consider staying because of the employee benefits of a mastery climate for improving their work life quality.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar vein, Steele-Johnson, Heintz, and Miller (2008) showed that, relative to those with no LGO, people with LGO tended to perceive tasks as more challenging and showed better performance when they possessed the necessary cognitive ability. Lin and Chang (2005) found that learning-oriented employees in sales departments were more likely to receive a promotion because they accumulated experiential knowledge and demonstrated better capability and performance. Payne, Youngcourt, and Beaubien (2007) conducted a meta-analysis and found that the effects of goal orientations on performance may vary across different task types, necessitating the differentiation of performance outcomes.…”
Section: Learning Goal Orientation and Innovative Performancementioning
confidence: 99%
“…In a similar vein, Steele‐Johnson, Heintz, and Miller () showed that, relative to those with no LGO, people with LGO tended to perceive tasks as more challenging and showed better performance when they possessed the necessary cognitive ability. Lin and Chang () found that learning‐oriented employees in sales departments were more likely to receive a promotion because they accumulated experiential knowledge and demonstrated better capability and performance.…”
Section: Learning Goal Orientation and Innovative Performancementioning
confidence: 99%
“…levels of employee turnover may impede the quality, consistency and stability of services that organizations provide to clients and customers (Trevor and Nyberg 2008) and in turn increased client dissatisfaction with the services provided by the organization (Lin and Chang 2005).…”
mentioning
confidence: 99%